The effect of growth hormone on ovarian function recovery in a mouse model of ovarian insufficiency - Kim, Su Mi; Yoo, Jung Young; Hong, Yeon Hee; Lee, Jaewang; Kim, Ji Hyang; Lee, Jung Ryeol (Frontiers in Endocrinology, 2023)
To evaluate the effects and mechanisms of action of growth hormone (GH) in the recovery of ovarian function in ovarian insufficiency induced by cyclophosphamide (CP) in a mouse model.After inducing ovarian insufficiency by administering 400 mg/kg of CP intraperitoneally to 6-week-old ICR mice, the mice were divided into four groups (control, CP, 1 mg/kg GH, and 2 mg/kg GH) with 10 mice in each group. GH was administered a week later for 7 days. Five mice from each group were sacrificed the next day, and their ovaries were collected for histological examination. The remaining mice were superovulated for in vitro fertilization (IVF). The terminal deoxynucleotidyl transferase dUTP-nick end labeling assay was performed to detect apoptosis. Masson's trichrome staining was used to analyze the degree of fibrosis. To quantify angiogenesis, CD31 immunohistochemistry was performed. Angiogenesis-related gene expression profiles were assessed using quantitative reverse transcription polymerase chain reaction.Results: CP induced the loss of non-growing (primordial and primary) follicles while GH significantly protected primordial follicles and increased follicular quality. The CP group showed a decrease in fertilization and blastocyst formation rates in IVF. In contrast, the GH treatment group showed dose-dependent enhanced IVF outcomes. Furthermore, GH treatment decreased apoptosis and stromal fibrosis and increased angiogenesis. Many genes involved in angiogenesis, especially Leptin (Lep), platelet endothelial cell adhesion molecule 1 (Pecam-1), and angiogenin (Ang) were upregulated in the GH treatment groups.GH treatment may promote the recovery of ovarian function in ovarian insufficiency induced by the administration of CP via decreasing apoptosis and stromal fibrosis and upregulating Lep, Pecam-1, and Ang genes.